Collaborative Governance Berbasis Pentahelix dalam Pengembangan Desa Wisata Berkelanjutan (Studi Kasus: Desa Wisata Taro, Kecamatan Tegallalang, Kabupaten Gianyar) - Ida Ayu Dewi Indrayani; Ni Putu Anik Prabawati; I Putu Dharmanu Yudartha (CV. Lenggogeni Data Publishing, 2024)
This research aims to find out the extent of implementationCollaborative Governance Based on Pentahelix in Sustainable Tourism Village Development (Case Study: Taro Tourism Village, Tegallalang District, Gianyar Regency). In this research, the author used a qualitative research method with a descriptive approach. The analysis in this research is based on success measurement theory collaborative governance according to DeSeve in Sudarmo, (2011). The results of the research findings show that collaboration between pentahelix actors, namely government, academics, community, business and media has gone quite well, but there are still several things that are problems, such as limitations in resource utilization. There are limited human resources in exploring potential in the tourism sector and the marketing methods used in developing tourist villages are still less than optimal. The recommendations that can be given are from government actors who are expected to further intensify pentahelix collaboration to continue increasing human resource potential. There is a need for synergy in developing promotion-related innovations to improve sustainable marketing of the Taro Tourism Village. Striving for the sustainability of tourist villages by strengthening and representing them tagline Taro Tourism Village is